Digital Public Relations Dalam Pemanfaatan Program Keluarga Harapan (PKH) Kementerian Sosial RI - Ahmad Haikal Kahfi; Winda Dwi Astuti Zebua (Institut Nalanda, 2024)
As an agent to serve the needs of the community, the Ministry of Social Affairs is expected and required to have good work productivity in serving the community so that the continuity of an institution/organization must maintain its trust. To support the Ministry of Social Affairs in its communication services, it must be able to achieve unidirectional or effective communication by using the digital public relations communication model to achieve its targets directly. The Ministry of Social Affairs provides social assistance called the family hope program. This program aims to alleviate poverty in Indonesian society, in various categories of social assistance. This type of research is field research with a qualitative descriptive method. Determining subjects used non-probability sampling with purposeful sampling. The number of informants was 4 people, namely staff from the Ministry of Social Affairs, practitioners of the Indonesian Ministry of Social Affairs' Family Hope Program and Digital Public Relations Lecturers. Data collection techniques used interviews and documentation. The results of the interviews revealed that the Ministry of Social Affairs' digital utilization method in the family hope program built by the Ministry of Social Affairs had been well developed. However, there are several things that must be addressed in order to strengthen public trust in the content presented by the Ministry of Social Affairs.customers.